1998
DOI: 10.1042/bj3340189
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction by epidermal growth factor and heregulin via the kinase-deficient ErbB3 protein

Abstract: The role of protein tyrosine kinase activity in ErbB3-mediated signal transduction was investigated. ErbB3 was phosphorylated in vivo in response to either heregulin (HRG) in cells expressing both ErbB3 and ErbB2, or epidermal growth factor (EGF) in cells expressing both ErbB3 and EGF receptor. A recombinant receptor protein (ErbB3-K/M, in which K/M stands for Lys-->Met amino acid substitution) containing an inactivating mutation in the putative ATP-binding site was also phosphorylated in response to HRG and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 62 publications
5
81
0
Order By: Relevance
“…Signal transduction to SHC from ERBB3 occurs after NRG or EGF exposure in NIH 3T3 cells. 106 Site-directed mutagenesis studies in these cells indicated that NRG stimulation of mitogenesis involved both MAPK and PI3K pathways from ERBB3, with the ERBB3 SHC-binding site at rat Tyr1325 essential for the MAPK pathway stimulation. 147,148 In MDA-MB-468 human mammary cancer cells, NRG1β preferentially stimulated ERBB3, resulting in recruitment of SHC.…”
Section: Proteins Binding With Phosphotyrosines In Erbb3′s Cytoplasmimentioning
confidence: 97%
See 2 more Smart Citations
“…Signal transduction to SHC from ERBB3 occurs after NRG or EGF exposure in NIH 3T3 cells. 106 Site-directed mutagenesis studies in these cells indicated that NRG stimulation of mitogenesis involved both MAPK and PI3K pathways from ERBB3, with the ERBB3 SHC-binding site at rat Tyr1325 essential for the MAPK pathway stimulation. 147,148 In MDA-MB-468 human mammary cancer cells, NRG1β preferentially stimulated ERBB3, resulting in recruitment of SHC.…”
Section: Proteins Binding With Phosphotyrosines In Erbb3′s Cytoplasmimentioning
confidence: 97%
“…104,109 However, in five human mammary and ovarian carcinoma cell lines expressing both receptors no EGFR tyrosine phosphorylation occurred after NRG treatment. 86 Interaction of ERBB3 with the ligand-less ERBB2 results in a complex with enhanced affinity for NRG and increased ERBB3 phosphorylation, 106,110,111 and these receptors, as noted below, contribute synergistically to cell transformation and to malignant properties of cancer cells. ERBB2 is more likely to heterodimerize with ERBB3 than to homodimerize.…”
Section: Erbb3 Interacting Proteins: Activation Signaling and Regulamentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of these observation we have considered the possibility that recruitment of Gab1 in response to FGF stimulation depends on FRS2␣. Because PI-3 kinase is one of the effectors of Gab1 (13,18), this could provide a mechanism for FGF-induced activation of PI-3 kinase. Moreover, it raises an intriguing possibility that FRS2␣ functions not only as a platform for recruitment of signaling proteins, but also as a signal for coordinated assembly of docking proteins that recruit an additional complement of effector proteins (Fig.…”
Section: Frs2␣ Is Required For Recruitment Of Pi-3 Kinase Via the Docmentioning
confidence: 99%
“…If FRS2␣ is required for tyrosine phosphorylation of Gab1, it is expected that FRS2␣ might play a role in activation of PI-3 kinase, because PI-3 kinase is one of the effectors that is recruited by Gab1 (13,18). To test this hypothesis, wild-type or FRS2␣-deficient fibroblasts were stimulated with FGF, and lysates from stimulated or unstimulated cells were subjected to immunoprecipitation with anti-Gab1 antibodies, followed by analysis of PI-3 kinase activity in anti-Gab1 immunoprecipitates (see Methods).…”
Section: Frs2␣ Is Required For Recruitment Of Pi-3 Kinase Via the Docmentioning
confidence: 99%